Failure Risk Analysis of Storage Tank Using the Risk-Based Inspection Method in a Biofuel Supply Company: Analisis Resiko Kegagalan Pada Storage Tank dengan Metode Risk Based Inspection - Idris, Mukandar; Aryanny, Enny (Universitas Muhammadiyah Sidoarjo, 2026)
Background (General) Storage tanks play a critical role in ensuring the continuity and safety of biodiesel distribution, where structural integrity is essential to prevent environmental, operational, and safety hazards. Background (Specific) At PT XYZ, recurring issues such as corrosion and leakage indicate limitations in the current time-based inspection approach. Knowledge Gap Previous studies applied RBI or AHP separately, but few integrated technical risk data with multi-criteria decision-making to produce an inspection and maintenance strategy that is both objective and operationally relevant. Aim This study aims to assess the risk level of a biodiesel storage tank using an integrated Risk-Based Inspection (RBI) and Analytic Hierarchy Process (AHP) approach to determine optimal inspection intervals and maintenance priorities. Results The analysis shows that critical subsystems—Storage Tank, Piping, Automatic Gauge Tank, PRV, and PVV—fall into high and extreme risk categories, with the overall tank risk classified as medium; corrosion analysis indicates remaining life values between 51–107 years, leading to a recommended inspection interval of four years instead of five. Novelty This study offers a combined RBI–AHP framework that aligns quantitative risk factors with managerial decision priorities. Implications The findings support more precise, risk-informed maintenance planning to enhance safety, reliability, and operational continuity in biodiesel storage operations. Highlights: Identifies high-risk subsystems requiring prioritized inspection. Integrates RBI–AHP to produce objective maintenance decisions. Recommends shorter inspection intervals to enhance operational safety. Keywords: Risk-Based Inspection, Analytic Hierarchy Process, Storage Tank, Corrosion, Maintenance Strategy